Meningkatkan Keterampilan Berbicara Bahasa Jawa melalui Permainan Dolanan Anak - Putri, Ema Efita; Purwandari, Septiyati; Triana , Putri Meinita (Asatiza: Jurnal Pendidikan, 2024)
Speaking skills are a means of developing children to interact and communicate with other people. Children's play games are games that develop in each particular region with the cultural background of that region. The aim of this research is to find out how children's play games can improve students' Javanese speaking skills. This type of research uses classroom action research. Data collection was carried out using observations, tests and field notes carried out in 2 cycles at Grow 4 Elementary School, Sewon, Bantul, Yogyakarta. The results of the research showed an increase in the average value of 50% then to 67.5% and ending in cycle II at 95%. From the average score, children achieve indicators of success in Javanese speaking skills.